The Study of the Impact of Complex Foliar Fertilization on the Yield and Quality of Sunflower Seeds (Helianhtus annuus L.) by Principal Component Analysis - Florin Crista; Isidora Radulov; Florinel Imbrea; Dan Nicolae Manea; Marius Boldea; Iosif Gergen; Anișoara Aurelia Ienciu; Ioan Bănățean Dunea (Agronomy, 2023)
The aim of the paper is to assess the impact of Foliar Fertilizations (FF) on the yield and quality of sunflower seeds. This research was carried out in the agricultural years of 2019–2021 in the experimental field of the university. The method of planting in the field was carried out in subdivided plots with three repetitions and six fertilization options. The experimental variants were as follows: Control (Mt), V1—FF 10:10:10+ME (microelements), V2—FF 8:10:0+8B (Boron)+ME, V3—FF 15:0:0+2S (Sulfur)+1B+ME, V4—FF 15:0:0+4B+ME, and V5—FF 8:8:8+ME. FF treatments were carried out in the vegetation phases specific to the sunflower crop. These varied from 2–6 L ha−1, depending on the chemical composition of the product. The application of treatments with FF to the sunflower culture positively influenced both production and its quality expressed by specific quality indices, namely the content of proteins, lipids, carbohydrates, fibers, and minerals. The results were discussed not only in view of classical statistics but also using the Principal Components Analysis (PCA), which allows a more complex evaluation of the effects of foliar treatments on the production and quality of sunflower seeds.